Evidence for healing of class II and class III furcations 24 months after guided tissue regeneration therapy: digital subtraction and clinical measurements - Eickholz, Peter; Hausmann, Ernest (Journal of periodontology, 1999)
The aim of this study was to compare bone regeneration as assessed by subtraction radiography with clinical attachment measurements 24 months after regenerative surgery.
Gesehen am 12.03.2021